Comptabilité et réalité financière : quelques observations autour d’un registre comptable de l’abbaye Saint-Amand de Rouen (1387/8-1397) - Isabelle Theiller (Tabularia)
The Benedictine abbey of Saint-Amand at Rouen preserves amongst its archives, now at Archives départementales de la Seine-Maritime, an account’s roll which during the period from 1387 to 1397 was annotated by several receivers. The account’s roll reveals the abbey’s financial crisis, the collapse of its seigneurial revenues and the receivers' attempt to rebuild the acount towards the end of the XIVth century.